Strategic Integration of Transport Modes for Global Supply Chain Optimization - Nur, Muhammad Zulfan; Tohir, Muhammad (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
Multimodal transportation, which involves the use of two or more modes of transport under a single contract, has evolved into the backbone of global supply chain efficiency. This journal presents an in-depth analysis of the theoretical foundation, operational principles, as well as the strategic implications and challenges in the implementation of multimodality, based on a synthesis of literature from leading experts in the fields of logistics and transportation. The discussion includes the central role of containerization, the development of transshipment infrastructure, the adoption of information technology, as well as the regulatory and policy frameworks that support it. The main focus is on how multimodality fundamentally changes the paradigm of goods movement, from fragmented to integrated, in order to achieve cost, time, reliability, and sustainability optimization.